The levels of urinary glycosaminoglycans of patients with attenuated and severe type of mucopolysaccharidosis II determined by liquid chromatography-tandem mass spectrometry - Mashima, Ryuichi (Mol Genet Metab Rep, 2016)
Glycosaminoglycans (GAGs) play important roles on the regulation of extracellular signaling, neuronal development, and cartilage maintenance. The extracellular concentration of total GAGs has been used as an established measure for the diagnosis of mucopolysaccharidoses (MPSs). Heparan sulfate (HS), Dermatan sulfate (DS) and chondroitin sulfate are known to be elevated in the GAGs under pathological conditions associated with MPS. Furthermore, the selective accumulation of disease-specific one of, or a combination of, them has also been used for the estimation of subtypes of MPS. A previously developed method [Auray-Blais C et al. Molecular Genetics and Metabolism 102 (2011) 49–56.] measures the concentration of GAGs using liquid chromatography with tandem mass spectrometry (LC-MS/MS) with higher precision. To ask whether the selective accumulation of HS and DS in the urine of MPS II patients discriminate the attenuated and severe type of MPS II, we examined the concentrations of HS and DS by this methodology. Compared to the healthy controls, we found a marked elevation of HS and DS in all of the MPS II-affected patients. Among patients who received ERT with confirmed elevation of antibody titer, the concentrations of HS in the urine of patients with attenuated type were lower than those with severe type of MPS II. In these patients, the concentrations of DS by LC-MS/MS and of total GAG by DMB failed to depend on the accumulation of antibody. These results suggest that the LC-MS/MS method employed in this study might discriminate the subtypes of MPS II in different clinical background.